A sulfide electrolyte, a lithium ion battery and a preparation method thereof

CN117430141BActive Publication Date: 2026-10-09WUHAN UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311477148.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-07
Publication Date
2026-10-09
Estimated Expiration
2043-11-07

AI Technical Summary

Technical Problem

然而,硫化物电解质的空气稳定性差,硫化物电解质与空气中的水分反应而使得离子电导率下降,并且还会生成有毒的H2S气体,进而降低了硫化物电解质的使用寿命

Benefits of technology

[0021] This application provides a sulfide electrolyte, a lithium-ion battery, and a method for preparing the same. By introducing zinc and oxygen into the sulfide electrolyte, the air stability of the sulfide electrolyte is improved while maintaining its high ionic conductivity. Specifically, oxygen is introduced into the sulfide electrolyte, replacing some of the sulfur. This transforms some of the PSP bonds in the sulfide electrolyte into POP, thereby reducing the reaction of the PSP bonds with moisture in the air to generate H2S gas and improving the stability of the sulfide electrolyte in air. Furthermore, the zinc introduced into the sulfide electrolyte is a soft acid metal, which readily combines with sulfur, further enhancing the stability of the sulfide electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117430141B_ABST
    Figure CN117430141B_ABST
Patent Text Reader

Abstract

The application discloses a sulfide electrolyte, a lithium ion battery and a preparation method thereof. The preparation method comprises the following steps: mixing Li2S, P2S 5 , LiCl, LiBr and ZnO according to a preset molar ratio to obtain a first intermediate product; grinding the first intermediate product to obtain a second intermediate product; and performing heat treatment on the second intermediate product at a preset temperature for a preset time to obtain the sulfide electrolyte. The molecular formula of the sulfide electrolyte is Li 5.5 Zn x P 1‑ 0.4x S 4.5‑x Cl 0.75 O x Br 0.75 (0 < x < 0.1). The sulfide electrolyte, the lithium ion battery and the preparation method thereof provided by the application can improve the air stability of the sulfide electrolyte while maintaining a high ion conductivity of the sulfide electrolyte by introducing zinc and oxygen into the sulfide electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium-ion batteries, and more specifically, to a sulfide electrolyte, a lithium-ion battery, and a method for preparing the same. Background Technology

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and other fields due to their high energy density and high capacity. Traditional lithium-ion batteries use liquid electrolytes, but liquid electrolytes have a low flash point, which can lead to spontaneous combustion, or even explosions, under abnormal conditions such as high-current discharge, overcharging, or internal short circuits. Solid-state lithium-ion batteries use non-flammable or non-flammable solid electrolytes instead of the flammable organic electrolytes in traditional lithium-ion batteries, fundamentally solving the safety problems of lithium-ion batteries. Solid-state electrolytes used in solid-state lithium-ion batteries have become a focus of research and development in recent years.

[0003] Among various solid electrolytes, sulfide electrolytes have attracted widespread attention due to their extremely high room-temperature ionic conductivity and processability. However, sulfide electrolytes have poor air stability; they react with moisture in the air, causing a decrease in ionic conductivity and generating toxic H2S gas, thereby reducing their service life.

[0004] Therefore, there is an urgent need for a sulfide electrolyte with good air stability and high ionic conductivity. Summary of the Invention

[0005] This application provides a sulfide electrolyte, a lithium-ion battery, and a method for preparing the same. The sulfide electrolyte exhibits good air stability and high ionic conductivity.

[0006] To solve one or more of the above-mentioned technical problems, the technical solution adopted in this application is:

[0007] In a first aspect, this application provides a method for preparing a sulfide electrolyte, the method comprising:

[0008] The first intermediate product was obtained by mixing Li2S, P2S5, LiCl, LiBr, and ZnO in a predetermined molar ratio.

[0009] The first intermediate product is ground to obtain the second intermediate product;

[0010] The second intermediate product is heat-treated at a preset temperature for a preset time to obtain the sulfide electrolyte, the molecular formula of which is Li. 5.5 Zn x P 1-0.4x S 4.5-x Cl 0.75 Ox Br 0.75 (0 < x ≤ 0.1).

[0011] Furthermore, the crystal structure of the sulfide electrolyte is that of silver-germanium sulfide.

[0012] Furthermore, the preset molar ratio is 4∶(1-0.4x)∶1.5∶1.5∶2x.

[0013] Furthermore, the grinding process includes high-energy ball milling.

[0014] Furthermore, the high-energy ball mill operates at a speed of 500-600 rpm.

[0015] Furthermore, the high-energy ball milling time is 16-20 hours.

[0016] Furthermore, the preset temperature is 430-500℃.

[0017] Furthermore, the preset time is 6-15 hours.

[0018] Secondly, this application also provides a sulfide electrolyte, wherein the sulfide electrolyte is a sulfide electrolyte prepared by the above-described preparation method.

[0019] Thirdly, this application also provides a lithium-ion battery, the lithium-ion battery comprising a positive electrode, a negative electrode and an electrolyte located between the positive electrode and the negative electrode, the electrolyte being the aforementioned sulfide electrolyte.

[0020] According to the specific embodiments provided in this application, the following technical effects are disclosed:

[0021] This application provides a sulfide electrolyte, a lithium-ion battery, and a method for preparing the same. By introducing zinc and oxygen into the sulfide electrolyte, the air stability of the sulfide electrolyte is improved while maintaining its high ionic conductivity. Specifically, oxygen is introduced into the sulfide electrolyte, replacing some of the sulfur. This transforms some of the PSP bonds in the sulfide electrolyte into POP, thereby reducing the reaction of the PSP bonds with moisture in the air to generate H2S gas and improving the stability of the sulfide electrolyte in air. Furthermore, the zinc introduced into the sulfide electrolyte is a soft acid metal, which readily combines with sulfur, further enhancing the stability of the sulfide electrolyte.

[0022] Of course, any product implementing this application does not necessarily need to achieve all of the advantages described above at the same time. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 A flowchart illustrating the preparation method of the sulfide electrolyte provided in this application embodiment;

[0025] Figure 2 The XRD patterns are of the sulfide electrolytes prepared in Examples 1-4 of this application;

[0026] Figure 3 The graph shows the variation of the ionic conductivity of the sulfide electrolytes provided in Examples 1-4 of this application with different ZnO doping contents.

[0027] Figure 4 The graph shows the variation of H2S gas content released by the sulfide electrolytes prepared in Comparative Example 1 and Examples 1-4 as they were exposed to air with the same humidity for different periods of time. Detailed Implementation

[0028] The technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art are within the scope of protection of this application.

[0029] As described in the background section, sulfide electrolytes have poor air stability. Sulfide electrolytes react with moisture in the air, which reduces their ionic conductivity and generates toxic H2S gas, thereby reducing the service life of sulfide electrolytes.

[0030] To address one or more of the aforementioned problems, this application proposes a sulfide electrolyte, a lithium-ion battery, and a method for preparing the same. By introducing zinc and oxygen elements into the sulfide electrolyte, the air stability of the sulfide electrolyte is improved while maintaining its high ionic conductivity.

[0031] Figure 1 This is a flowchart illustrating the preparation method of the sulfide electrolyte provided in the embodiments of this application, as shown below. Figure 1 As shown, a method for preparing a sulfide electrolyte includes:

[0032] S1: Li2S, P2S5, LiCl, LiBr, and ZnO are mixed in a predetermined molar ratio to obtain the first intermediate product.

[0033] In the prior art, sulfide electrolytes have attracted widespread attention due to their extremely high room-temperature ionic conductivity and processability. However, sulfide electrolytes suffer from poor air stability, reacting with moisture in the air to reduce ionic conductivity and generating toxic H2S gas, thereby shortening their service life. This application aims to improve the air stability of sulfide electrolytes while maintaining their high ionic conductivity by introducing zinc and oxygen elements into existing sulfide electrolytes.

[0034] Specifically, oxygen is introduced into the sulfide electrolyte, replacing some of the sulfur. This means that some of the PSP bonds in the sulfide electrolyte are transformed into POP, thereby reducing the reaction of the PSP bonds in the sulfide electrolyte with moisture in the air to generate H2S gas and improving the stability of the sulfide electrolyte in the air. On the other hand, the zinc element introduced into the sulfide electrolyte is a soft acid metal element, which easily combines with sulfur, further improving the stability of the sulfide electrolyte.

[0035] S2: Grind the first intermediate product to obtain the second intermediate product.

[0036] This application does not impose special requirements on the grinding method and process. Any known grinding method can be used in this application without departing from the inventive concept. It is merely an illustrative example and not a limitation on the scope of protection. Grinding can be performed by high-energy ball milling. In the embodiments of this application, the grinding is high-energy ball milling. Preferably, the rotation speed of the high-energy ball mill is 500-600 rpm, and the high-energy ball milling time is 16-20 hours.

[0037] S3: The second intermediate product is heat-treated at a preset temperature for a preset time to obtain the sulfide electrolyte, the molecular formula of which is Li. 5.5 Zn x P 1-0.4x S 4.5-x Cl 0.75 O x Br 0.75 (0 < x ≤ 0.1).

[0038] Furthermore, x can be 0.01, 0.03, 0.05, 0.07, 0.09, or 0.1, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values ​​included in the range.

[0039] In one specific implementation, the preset molar ratio is 4∶(1-0.4x)∶1.5∶1.5∶2x, where as mentioned above, 0<x≤0.1.

[0040] Since Akitoshi Hayashi et al. discovered that doping Li3PS4 solid electrolyte with 10 mol% ZnO can effectively reduce the generation of H2S gas and achieve a relatively high ionic conductivity, -4 S cm -1 (Journal of Materials Chemistry A, 2013, 1, 6320-6326). Therefore, existing sulfide solid electrolytes usually select zinc oxide with a molar ratio of about 10% for doping in order to obtain higher room temperature ionic conductivity.

[0041] This application unexpectedly discovered that even when the molar ratio of zinc oxide doping is less than 2.44% (x = 0.1), it is still possible to significantly reduce H2S gas production while simultaneously achieving high ionic conductivity. -3 S cm -1 As shown above, the ionic conductivity of the sulfide solid electrolyte increases significantly as x decreases from 0.1. It is evident that this application, by mixing Li₂S, P₂S₅, LiCl, LiBr, and ZnO in a preset molar ratio of 4:(1-0.4x):1.5:1.5:2x and then heat-treating at a preset temperature and time, demonstrates that a specific molar ratio of zinc oxide can not only stabilize the sulfide solid electrolyte but also achieve high ionic conductivity. Furthermore, the relatively low doping ratio of zinc oxide reduces the stringent requirements for grinding, temperature, and time in solid electrolyte production, providing an important pathway for the large-scale production of sulfide solid electrolytes.

[0042] In a preferred embodiment, the crystal structure of the sulfide electrolyte is that of silver-germanium sulfide ore.

[0043] This application does not impose any special limitations on the heat treatment method; any heat treatment method known to those skilled in the art is acceptable. In the embodiments of this application, the preset temperature for heat treatment is 430-500℃. More specifically, the preset temperature can be 430℃, 440℃, 450℃, 460℃, 470℃, 480℃, 490℃, or 500℃, as well as specific values ​​between these values. For space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values ​​included in the range. The preset time is 6-15 hours. More specifically, the preset time can be 6, 8, 10, 12, 14, or 15 hours, as well as specific values ​​between these values. For space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values ​​included in the range.

[0044] This application also provides a sulfide electrolyte, which is a sulfide electrolyte prepared by the above-described method. Because zinc and oxygen elements are introduced into the sulfide electrolyte provided in this application, the air stability of the sulfide electrolyte is improved while maintaining its high ionic conductivity.

[0045] This application also provides a lithium-ion battery, which includes a positive electrode, a negative electrode, and an electrolyte located between the positive electrode and the negative electrode, wherein the electrolyte is the sulfide electrolyte described above.

[0046] In this embodiment of the application, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on the surface of the negative current collector. The negative active material layer includes a negative binder, a negative active material, and a negative conductive agent.

[0047] This application does not impose any particular limitation on the negative electrode current collector. As long as it is conductive and does not cause chemical changes in the battery, it is acceptable, provided that it does not violate the inventive concept of this application.

[0048] Optionally, the shape of the negative electrode current collector may include a foil shape, a plate shape, or a mesh shape.

[0049] Optionally, the negative electrode current collector includes any one of aluminum, copper, nickel, or zinc.

[0050] Optionally, the negative electrode current collector includes any one of aluminum, copper, nickel, or zinc alloy.

[0051] Negative electrode binder is a polymer compound used to adhere the negative electrode active material to the negative electrode current collector. Its main function is to bond and retain the negative electrode active material, enhance the contact between the negative electrode active material and the negative electrode conductive agent, and between the negative electrode active material and the negative electrode current collector, thereby better stabilizing the structure of the negative electrode sheet. The negative electrode binder includes, but is not limited to, polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene-ethylene-butene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate, etc. Users can choose according to their actual needs; no specific limitations are made here.

[0052] This application does not specifically limit the type of negative electrode active material. Any known negative electrode active material can be used in this application without departing from the inventive concept. In one embodiment, the negative electrode active material includes lithium metal and / or lithium alloys. In other embodiments, the negative electrode active material is a silicon-based negative electrode active material containing silicon, such as silicon alloys, silicon oxide, or combinations thereof, and in some cases, it may be mixed with graphite. In other embodiments, the negative electrode active material may include carbon-based negative electrode active materials containing one or more of graphite, graphene, carbon nanotubes (CNTs), and combinations thereof. In yet another embodiment, the negative electrode active material includes one or more lithium-accepting negative electrode active materials, such as lithium titanium oxide (Li4Ti5O). 12 One or more transition metals (such as tin (Sn)), one or more metal oxides (such as vanadium oxide (V2O5), tin oxide (SnO), titanium dioxide (TiO2)), titanium niobium oxide (Ti) x Nb y O z , where 0≤x≤2, 0≤y≤24 and 0≤z≤64, metal alloys (such as copper-tin alloy (Cu6Sn5)) and one or more metal sulfides (such as iron sulfide (FeS)).

[0053] The negative electrode conductive agent may include carbon-based materials, powdered nickel or other metal particles, or conductive polymers. Carbon-based materials may include particles such as carbon black, graphite, super-P, acetylene black (such as KETCHENTM black or DENKATM black), carbon fibers and single-walled carbon nanotubes (SWCNTs), graphene, etc. Examples of conductive polymers include polyaniline, polythiophene, polyacetylene, polypyrrole, poly(3,4-ethylenedioxythiophene)polysulfonated styrene, etc.

[0054] The above materials are merely illustrative examples of the selected negative electrode materials. It is understood that any known negative electrode material, including negative electrode binders, negative electrode active materials, negative electrode conductive agents, and other additives, can be used in this application without departing from the inventive concept of this application.

[0055] In this embodiment, the positive electrode sheet includes a positive current collector and a positive active material layer covering the surface of the positive current collector. The positive active material layer includes a positive active material, a positive binder, and a positive conductive agent. Specifically, the positive active material, positive binder, positive conductive agent, and solvent are mixed uniformly to obtain a positive slurry. The positive slurry is then coated onto the surface of the positive current collector, dried, and rolled to obtain the positive electrode sheet.

[0056] In this application embodiment, there are no particular limitations on the positive electrode current collector, as long as it is conductive and does not cause chemical changes in the battery. Specifically, the positive electrode current collector includes, but is not limited to, any one of aluminum, nickel, or stainless steel, such as aluminum foil. The shape of the positive electrode current collector includes, but is not limited to, metal foil, metal grid, metal mesh, etc., and users can choose according to actual needs; no specific limitation is made here.

[0057] The positive electrode active material is a compound that can reversibly insert and deintercalate lithium. The positive electrode active material in this application can be any positive electrode active material known in the art. For example, the positive electrode active material includes, but is not limited to, one of layered oxide cathodes, spinel cathodes, olivine-type cathodes, and polyanionic cathodes. For example, a layered oxide cathode (e.g., rock salt layered oxide) comprises one or more lithium-based positive electrode active materials selected from: LiCoO2 (LCO), LiNi x Mn y Co 1-x- y O2 (where 0 ≤ x ≤ 1 and 0 ≤ y ≤ 1), LiNi 1-x-y Co x Al y O2 (where 0 ≤ x ≤ 1 and 0 ≤ y ≤ 1), LiNi x Mn 1-x O2 (where 0 ≤ x ≤ 1), and Li l+x MO2 (where M is one of Mn, Ni, Co, and Al and 0 ≤ x ≤ 1). The spinel cathode comprises one or more lithium-based positive electrode active materials selected from the following: LiMn2O4 (LMO) and LiNi. x Mn 1.5 O4. The olivine-type cathode comprises one or more lithium-based positive electrode electroactive materials, LiMPO4 (where M is at least one of Fe, Ni, Co, and Mn). The polyanionic cation comprises, for example, phosphates such as LiV2(PO4)3 and / or silicates such as LiFeSiO4.

[0058] In one specific embodiment, based on the total weight of the solid components in the positive electrode slurry, the mass fraction of the positive electrode active material is 80%-99%. More specifically, the mass fraction of the positive electrode active material can be 80%, 85%, 90%, 95%, or 99%, as well as specific values ​​between these ranges. For space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values ​​included in the range. When the mass fraction of the positive electrode active material is below 80%, the reduced energy density will lead to a decrease in the capacity of the lithium-ion battery.

[0059] The positive electrode binder is a component that facilitates the adhesion between the positive electrode active material and the positive electrode conductive agent, as well as the adhesion to the positive electrode current collector. In the embodiments of this application, the positive electrode binder includes, but is not limited to, one or more of the following: polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene-ethylene-butene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, and lithium alginate. Users can choose according to their actual needs; no specific limitations are made here.

[0060] A positive electrode conductive agent is a material that provides conductivity without causing adverse chemical reactions in the battery. In embodiments of this application, the positive electrode conductive agent may include carbon-based materials, powdered nickel or other metal particles, or conductive polymers. Carbon-based materials may include particles such as carbon black, graphite, Super-P, acetylene black (e.g., KETCHENTM black or DENKATM black), carbon fibers and nanotubes, graphene, etc. Examples of conductive polymers include polyaniline, polythiophene, polyacetylene, polypyrrole, poly(3,4-ethylenedioxythiophene)polysulfonated styrene, etc. Preferably, the positive electrode conductive agent includes one or more of conductive carbon black (Super-P), acetylene black, Ketjen black, carbon nanotubes (CNTs), graphene (rGO), activated carbon, and carbon nanofibers (CNFs).

[0061] In one specific embodiment, based on the total weight of the solid components in the positive electrode slurry, the mass fraction of the positive electrode conductive agent is 1%-20%. More specifically, the mass fraction of the positive electrode conductive agent can be 1%, 5%, 10%, 15%, or 20%, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values ​​included in the range.

[0062] The solvent includes water or an organic solvent, such as N-methyl-2-pyrrolidone (NMP) or an alcohol, the amount of which allows the positive electrode slurry containing the positive electrode active material, positive electrode binder, and positive electrode conductive agent to achieve the desired viscosity. In one specific embodiment, the solvent content results in a solid component mass fraction of 15%-65% in the positive electrode slurry. More specifically, the solid component mass fraction in the positive electrode slurry can be 15%, 20%, 30%, 40%, 50%, or 65%, and specific values ​​between these values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list all the specific values ​​included in the range.

[0063] The above materials are merely illustrative examples of the selected positive electrode materials. It is understood that any known positive electrode material, including positive electrode binders, positive electrode active materials, positive electrode conductive agents, and other additives, can be used in this application without departing from the inventive concept of this application.

[0064] The embodiments of the present invention will be described in more detail below through examples. However, the embodiments of the present invention are not limited to these examples.

[0065] Example 1

[0066] A method for preparing a sulfide electrolyte, the method comprising the following steps:

[0067] The first intermediate product was obtained by mixing Li₂S, P₂S₅, LiCl, LiBr, and ZnO in a molar ratio of 4:0.996:1.5:1.5:0.02.

[0068] The first intermediate product was subjected to high-energy ball milling for 16 hours to obtain the second intermediate product, wherein the high-energy ball milling speed was 500 rpm;

[0069] The second intermediate product was heat-treated at 450°C for 8 hours to obtain the sulfide electrolyte, the molecular formula of which is Li. 5.5 Zn 0.0i P 0.996 S 4.49 O 0.01 Cl 0.75 Br 0.75 The ionic conductivity of this sulfide electrolyte was tested to be 8.80 mS / cm. -1 .

[0070] Example 2

[0071] A method for preparing a sulfide electrolyte, the method comprising the following steps:

[0072] The first intermediate product was obtained by mixing Li₂S, P₂S₅, LiCl, LiBr, and ZnO in a molar ratio of 4:0.988:1.5:1.5:0.06.

[0073] The first intermediate product was subjected to high-energy ball milling for 16 hours to obtain the second intermediate product, wherein the high-energy ball milling speed was 500 rpm;

[0074] The second intermediate product was heat-treated at 450°C for 8 hours to obtain the sulfide electrolyte, the molecular formula of which is Li. 5.5 Zn 0.03 P 0.988 S 4.47 O 0.03Cl 0.75 Br 0.75 The ionic conductivity of this sulfide electrolyte was tested to be 6.65 mS / cm. -1 .

[0075] Example 3

[0076] A method for preparing a sulfide electrolyte, the method comprising the following steps:

[0077] The first intermediate product was obtained by mixing Li₂S, P₂S₅, LiCl, LiBr, and ZnO in a molar ratio of 4:0.98:1.5:1.5:0.1.

[0078] The first intermediate product was subjected to high-energy ball milling for 16 hours to obtain the second intermediate product, wherein the high-energy ball milling speed was 500 rpm;

[0079] The second intermediate product was heat-treated at 450°C for 8 hours to obtain the sulfide electrolyte, the molecular formula of which is Li. 5.5 Zn 0.05 P 0.98 S 4.45 O 0.05 Cl 0.75 Br 0.75 The ionic conductivity of this sulfide electrolyte was tested to be 4.93 mS / cm. -1 .

[0080] Example 4

[0081] A method for preparing a sulfide electrolyte, the method comprising the following steps:

[0082] The first intermediate product was obtained by mixing Li₂S, P₂S₅, LiCl, LiBr, and ZnO in a molar ratio of 4:0.96:1.5:1.5:0.2.

[0083] The first intermediate product was subjected to high-energy ball milling for 16 hours to obtain the second intermediate product, wherein the high-energy ball milling speed was 500 rpm;

[0084] The second intermediate product was heat-treated at 450°C for 8 hours to obtain the sulfide electrolyte, the molecular formula of which is Li. 5.5 Zn 0.1 P 0.96 S 4.4 O 0.1 Cl 0.75 Br 0.75 The ionic conductivity of this sulfide electrolyte was tested to be 3.46 mS / cm. -1 .

[0085] Comparative Example 1

[0086] A method for preparing a sulfide electrolyte, the method comprising the following steps:

[0087] The first intermediate product was obtained by mixing Li₂S, P₂S₅, LiCl, and LiBr in a molar ratio of 4:1:1.5:1.5.

[0088] The first intermediate product was subjected to high-energy ball milling for 16 hours to obtain the second intermediate product, wherein the high-energy ball milling speed was 500 rpm;

[0089] The second intermediate product was heat-treated at 450°C for 8 hours to obtain a sulfide electrolyte, the molecular formula of which is Li. 5.5 PS 4.5 Cl 0.75 Br 0.75 .

[0090] The ionic conductivity and air stability of the samples from each embodiment and comparative example were tested, and the test results are as follows:

[0091] 1) Figure 2 The XRD patterns of the sulfide electrolytes prepared in Examples 1-4 show that, in Examples 1-4, the characteristic peaks gradually increase with the gradual increase of ZnO doping amount.

[0092] 2) Figure 3 The graphs showing the variation of ionic conductivity of the sulfide electrolytes provided in Examples 1-4 of this application with different ZnO doping contents reveal that within a certain range, as the ZnO doping content increases, P and S are gradually replaced. The inventors speculate that the migration path and transport rate of lithium ions may be affected, resulting in a decreasing trend in ionic conductivity.

[0093] 3) Figure 4 The graph shows the change in H2S gas content released by the sulfide electrolytes prepared in Comparative Example 1 and Examples 1-4 as they were exposed to air with the same humidity for different durations. It can be seen that the sulfide electrolyte in Comparative Example 1 has poor air stability, producing a large amount of H2S gas during the 30-minute test period. In contrast, the sulfide electrolytes in Examples 1-4, which introduced zinc and oxygen elements, produced less H2S gas during the 30-minute test period, indicating that the air stability of the sulfide electrolytes with the introduction of zinc and oxygen elements was effectively improved.

[0094] As can be seen from the above, the embodiments of this application provide a sulfide electrolyte, a lithium-ion battery and a method for preparing the same. By introducing zinc and oxygen elements into the sulfide electrolyte, the air stability of the sulfide electrolyte is improved while maintaining the high ionic conductivity of the sulfide electrolyte.

[0095] The foregoing has provided a detailed description of a sulfide electrolyte, a lithium-ion battery, and a method for preparing the same, as provided in this application. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of these embodiments are merely for the purpose of helping to understand the method and its core ideas. Furthermore, those skilled in the art will recognize that, based on the ideas of this application, there will be changes in the specific implementation methods and application scope. Therefore, the content of this specification should not be construed as a limitation of this application.

Claims

1. A method for preparing a sulfide electrolyte, characterized in that, The preparation method includes: The first intermediate product is obtained by mixing Li2S, P2S5, LiCl, LiBr, and ZnO in a preset molar ratio of 4:(1-0.4x):1.5:1.5:2x. The first intermediate product is ground to obtain the second intermediate product; Subjecting said second intermediate product to heat treatment at a preset temperature for a preset time to obtain said sulfide electrolyte, the molecular formula of said sulfide electrolyte is Li 5.5 Zn x P 1-0.4x S 4.5-x Cl 0.75 O x Br 0.75 (0 < x ≤ 0.1), and said preset temperature is 430-500°C.

2. The method for preparing the sulfide electrolyte according to claim 1, characterized in that, The crystal structure of the sulfide electrolyte is that of silver-germanium sulfide ore.

3. The method for preparing the sulfide electrolyte according to claim 1, characterized in that, The grinding process includes high-energy ball milling.

4. The method for preparing the sulfide electrolyte according to claim 3, characterized in that, The high-energy ball mill rotates at a speed of 500-600 rpm.

5. The method for preparing the sulfide electrolyte according to claim 3, characterized in that, The high-energy ball milling time is 16-20 hours.

6. The method for preparing the sulfide electrolyte according to claim 1, characterized in that, The preset time is 6-15 hours.

7. A sulfide electrolyte, characterized in that, The sulfide electrolyte is prepared by the method described in any one of claims 1 to 6.

8. A lithium-ion battery, characterized in that, The lithium-ion battery includes a positive electrode, a negative electrode, and an electrolyte, wherein the electrolyte is the sulfide electrolyte as described in claim 7.